Analisis Psikometrik Instrumen Grit (Grit-O): Studi pada Mahasiswa Sarjana Tahun Kedua dan Ketiga Masa Studi di Indonesia - Az Zahra, Dhiya; Ariyani, Mira; Suryaratri, Ratna Dyah (Universitas Darul Ulum, 2025)
Mid-year college students often face a challenging academic transition marked by increased workload, career pressure, and declining intrinsic motivation, which may lead to reduced engagement and a higher risk of dropout. Grit defined as perseverance and consistency toward long-term goals, emerges as a crucial psychological protective factor. This study aims to evaluate the validity and reliability of the Indonesian version of the Grit Scale (Grit-O) to ensure its cultural relevance and psychometric soundness for use among mid-year college students. Grit measures two dimensions Perseverance of Effort and Consistency of Interest (Duckworth et al., 2007). The adaptation process followed the International Test Commission (ITC) guidelines, including obtaining permission, back-to-back translations, evaluating language comparability and interpretability, and pilot testing on a student sample. 222 active students in greater area were recruited using convience sampling. Construct validity was assessed using confirmatory factor analysis (CFA), and internal reliability was examined with Cronbach’s alpha. The CFA results CFI = 0.920, TLI = 0.910, RMSEA = 0.060, with all subscales showing adequate reliability (α = 0.780). These findings indicate that the Indonesian version of the Grit-O scale is a valid and reliable instrument for assessing perceived social support among Indonesian mid year college students.